1982
DOI: 10.3382/ps.0612083
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Protein Level and Monensin on Performance of Chicks

Abstract: Four experiments were conducted to investigate a possible interaction between dietary protein level and monensin on growth performance of young chicks. Crossbred chicks (New Hampshire X Columbian) or commercial broiler chicks (Hubbard X Hubbard) were fed corn-soybean meal diets containing various protein levels with or without added monensin (160 or 121 mg/kg). Monensin had little or no effect on growth performance of crossbred chicks fed diets containing 24 or 20% protein. However, growth performance of chick… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 7 publications
2
22
0
2
Order By: Relevance
“…According to other data, the effect of monensin on food efficiency is not consistent. It was not affected in studies reported by Christmas and Harms (1984), Welch et al (1986) and Bartov (1987), while in others (Bartov and Jensen, 1980;Parsons and Baker, 1982;Parsons et al, 1984;Bartov, 1987) C, E and R: nutrient consumed, excreted and retained, respectively. 4 RR: relative retention.…”
Section: Discussionmentioning
confidence: 46%
See 2 more Smart Citations
“…According to other data, the effect of monensin on food efficiency is not consistent. It was not affected in studies reported by Christmas and Harms (1984), Welch et al (1986) and Bartov (1987), while in others (Bartov and Jensen, 1980;Parsons and Baker, 1982;Parsons et al, 1984;Bartov, 1987) C, E and R: nutrient consumed, excreted and retained, respectively. 4 RR: relative retention.…”
Section: Discussionmentioning
confidence: 46%
“…In contrast, however, the adverse effect of monensin on the absolute retention of nitrogen (Table 3) was not caused merely by its effect in reducing food intake, because it also decreased the RR of nitrogen, probably by interfering with nitrogen metabolism. This finding may partly explain why the toxicity of monensin can be reduced by inceasing dietary protein concentration (Parsons and Baker, 1982;Parsons et al, 1984;Welch et al, 1986).…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…The effect of dietary protein on broiler performance was reported by Fraps as early as 1943 [31]. Parsons and Baker [32] found a positive growth rate attributable to increased dietary protein levels. In the current study, however, the magnitude of reduction in performance attributable to the reduction in dietary CP was greater for the RS strain than for the BS1 or BS2 strains, resulting in an interaction between strain and dietary CP level on BWG.…”
Section: Discussionmentioning
confidence: 95%
“…Courtens et al (1998) ont montré que la plupart des antibiotiques inhibent ou réduisent la spermatogenèse chez les petits ruminants (béliers et boucs). Par ailleurs, les anticoccidiens dans une ration déficitaire en protéines, sont responsables d'une baisse de gain de poids, consécutive à une baisse de la consommation d'eau et d'aliment, aussi observée chez le poulet lors d'utilisation simultanée de certains macrolides (érythromycine) et des sulfamides (Parson et Baker, 1982). Ces données restent partielles et limitées seulement à quelques anticoccidiens et à quelques espèces.…”
unclassified